Stereoscopic telepresence viewing system for remotely operated underwater robotic vehicle - Seet, Gerald (2020)
This paper describes the design, structure, and preliminary evaluation of an experimental Telepresence Viewing System (TVS) for Underwater Robotic Vehicle (URV) application. The Telepresence Viewing System enables an automatic projection of properly prepared and adapted underwater stereoscopic video images from the video cameras of the URV, into the operator’s visual field. This helps the operator’s vestibular and kinesthetic sensations to be coupled to the visual information from the URV. The developed TVS is an active camera system, consisting of two video cameras, a video synchronizer and a multiplexer. These are applied to produce analog stereoscopic video images, which are further converted to VGA format and processed to derive flicker free stereo images. An adaptive camera convergence/divergence control system is incorporated in the system to reduce geometric distortions of the image. A zooming control feature also has been added to improve the eye comfort. These features have been tested and verified in limited human assessment, showing lower levels of eyestrain and operator discomfort. The system has also been demonstrated to overcome constraints imposed by URV design requirements.